Fisetin Promotes Hair Growth by Augmenting TERT Expression - Kubo, Chisato; Ogawa, Mizuki; Uehara, Norihisa; Katakura, Yoshinori (Frontiers in Cell and Developmental Biology, 2020)
Although thinning hair and alopecia are not recognized as severe diseases, hair loss has implications for mental health and quality of life; therefore, a large number of studies have been carried out to develop novel hair growth agents. In the present study, we aimed to examine the potential of telomerase reverse transcriptase (TERT), because TERT overexpression in skin activates resting hair follicle bulge stem cells, which triggers initiation of a new hair follicle growth phase and promotes hair synthesis. To this end, we screened polyphenols that activate TERT expression in keratinocytes, and identified resveratrol and fisetin as strong hTERT-augmenting compounds. These polyphenols also regulate the gene expression of cytokines such as IGF-1, KGF, and TGF-β, and activate the β-catenin pathway, both of which play roles in promoting hair growth. We additionally showed that these polyphenols, especially fisetin, promoted hair growth from the shaved dorsal skin of mice, which suggests that these polyphenols activate the transition from telogen to anagen phase. Histological studies indicated that the dorsal skin of mice treated with these polyphenols contained numerous hair follicles and was thickened compared with that in control mice. Furthermore, on the dorsal skin of mice treated with resveratrol and fisetin, a number of proliferating cells (Ki67+ cells) were observed around the hair papilla. These results suggest that resveratrol and fisetin induce a shift from telogen to anagen in the hair follicle by causing differentiation and proliferation of hair follicle bulge stem cells, thus promoting hair growth.